Crystal structure of di-mu(N,S)-thiocyanato-bis[(N-benzylideneaniline-C-2,N)palladium(II)], [Pd(C6H4CH=NC6H5)(mu-SCN)](2) - Santana, A. M.; Netto, AVD; De Almeida, E. T.; Mauro, Antonio Eduardo [UNESP]; Souza, J.; Santos, RHA (R Oldenbourg Verlag, 2002)
C28H20N4Pd2S2, monoclinic, P12(1)/c1 (No. 14), a = 11.325(1) Angstrom, b = 13.530(1) Angstrom, c = 17.925(1) Angstrom, beta = 106.23(1)degrees, V = 2637.1 Angstrom(3), Z = 4, R-gt(F) = 0.052, wR(ref)(F-2) = 0.129, T = 293 K.